2019 Quota Data Update. (Policy Papers; Policy Paper ;, 2021)
The paper presents summary results for the updated data set, with country-by-country details provided in Appendix I. In terms of broad country groups, the results of the data update are broadly consistent with trends observed in previous updates. The aggregate share of Emerging Market and Developing Countries (EMDCs) increased by 0.3 pp, to 50.0 percent, following a small decline in the EMDCs' share recorded in the 2018 data update. The rising EMDC share reflected again foremost an increase for Asia. Most advanced economies recorded a small decrease in their calculated quota share using the current quota formula.